Technological change and opportunities for development as a moving target - Perez, Carlota (UN New YorkUS, 1999)
Provides an interpretation of development as a process of accumulation of technological and social capabilities in developing countries that is dependent upon their ability to take advantage of differnet and successive windows of opportunity.